2015
DOI: 10.1021/acsnano.5b03708
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Degradation in Macrophages: Live Nanoscale Monitoring and Understanding of Biological Pathway

Abstract: Despite numerous applications, the cellular-clearance mechanism of multiwalled carbon nanotubes (MWCNTs) has not been clearly established yet. Previous in vitro studies showed the ability of oxidative enzymes to induce nanotube degradation. Interestingly, these enzymes have the common capacity to produce reactive oxygen species (ROS). Here, we combined material and life science approaches for revealing an intracellular way taken by macrophages to degrade carbon nanotubes. We report the in situ monitoring of RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
134
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 50 publications
5
134
1
2
Order By: Relevance
“…Evidence for NADPH oxidase-dependent degradation of SWCNTs in vivo was also provided [160]. Moreover, Zhang et al [161] reported that carbon nanohorns also undergo partial degradation in macrophage-like cell lines (RAW264.7 and THP-1) and degradation of MWCNTs has also been reported recently using differentiated THP-1 cells as a model [162]. Importantly, in the studies cited above, degradation was shown to occur in a complex biological environment, i.e., in cell culture in the presence of fetal bovine serum, or in the lungs of mice, suggesting that bio-corona formation does not prevent degradation of carbon-based nanomaterials.…”
Section: Biodegradation Of Carbon-based Nanomaterialsmentioning
confidence: 98%
“…Evidence for NADPH oxidase-dependent degradation of SWCNTs in vivo was also provided [160]. Moreover, Zhang et al [161] reported that carbon nanohorns also undergo partial degradation in macrophage-like cell lines (RAW264.7 and THP-1) and degradation of MWCNTs has also been reported recently using differentiated THP-1 cells as a model [162]. Importantly, in the studies cited above, degradation was shown to occur in a complex biological environment, i.e., in cell culture in the presence of fetal bovine serum, or in the lungs of mice, suggesting that bio-corona formation does not prevent degradation of carbon-based nanomaterials.…”
Section: Biodegradation Of Carbon-based Nanomaterialsmentioning
confidence: 98%
“…However, O 2 − • and NO• can effectively react to yield peroxynitrite, whose oxidizing potency is sufficient to cause biodegradation (Ischiropoulos et al, 1992). In vitro , effective biodegradation capacity has been demonstrated for several types of macrophages such as RAW 264.7, THP-1, and human monocyte-derived macrophages (Kagan et al, 2014; Elgrabli et al, 2008, 2015; Zhang et al, 2015) (Table 1). Because peroxynitrite-dependent oxidation reactions are independent of the direct binding of the reactive protein intermediates with nanoparticles, the degradation process driven by macrophages is independent on the specific positioning of the oxidative machinery on the surface of nanoparticles.…”
Section: Oxidative Degradation Of Nanoparticles By Inflammatory Cellsmentioning
confidence: 99%
“…Recent evidence has also reported the possibility of the degradation of CNTs by cells, such as neutrophils, 32 microglia, 33 and macrophages. [34][35][36] Overall, the current data suggest that the toxicity of MWCNTs can be at least partly reduced or minimized by improving design strategies of short-length MWCNT with appropriate surface modifications that are feasible for degradation by cells after the delivery of loaded proteins or drugs.…”
mentioning
confidence: 90%